PENGARUH IMPLEMENTASI ISLAMIC CORPORATE GOVERNANCE DAN SHARIAH COMPLIANCE TERHADAP FINANCIAL STATEMENT FRAUD PADA BANK SYARIAH INDONESIA - Amrina Rosada; Risma Eryani; Maya Panorama; Aprilia Aprilia (JURNAL EKBIS, 2022)
This study intends to assess the effect of Shariah Compliance and Islamic Corporate Governance on fraud in Islamic banks. The independent variables used are Shariah Compliance with Islamic Income Ratio, Profit Sharing Ratio and Islamic Investment Ratio as a proxy and Islamic Corporate Governance. Fraud in Islamic banking is the variable. In this study, the population is Indonesian Sharia Commercial Banks (BSI) registered with Bank Indonesia from 2017 to 2019. Three Indonesian Islamic banks are used as examples in this study, with a three-year research period. Multiple regression analysis was used in this study, which was carried out with SPSS version 22. The results showed that Good Corporate Governance had no effect on Financial Statement Fraud